Síntese de controladores Takagi-Sugeno com taxa de convergência pré-especificada para sistemas sujeitos a retardo no tempo - Rafael Henrique Alves Gomes (2015)
This work proposes a design method of Takagi-Sugeno fuzzy controller for nonlinear systems subject to time-varying delay. The performance index of the controller is given by an exponential convergence rate, which is useful to indicate an estimative of the transient response time. The proposed method is developed based on Lyapunov-Krasovskii theory and linear matrix inequalities (LMIs). The Lyapunov-Krasovskii functional chosen is composed of exponential terms that are primordial to determine the exponential convergence rate. Finally, numerical experiments are presented to illustrate the efficiency of the proposed methodology.